2016
DOI: 10.1186/s12974-016-0557-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of transient receptor potential ankyrin 1 channels in Alzheimer’s disease

Abstract: BackgroundTransient receptor potential ankyrin 1 (TRPA1) channel plays an important role in pain and inflammation. However, little is known about the significance of the TRPA1 channel in the pathophysiology of Alzheimer’s disease (AD).MethodsWild-type (WT), TRPA1−/−, amyloid precursor protein (APP)/presenilin 1 (PS1) transgenic (APP/PS1 Tg) mice, the mouse model of AD, and APP/PS1 Tg/TRPA1−/− mice were used to examine the role of TRPA1 in pathogenesis of AD. Western blot was used for protein expression; immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 66 publications
1
57
1
Order By: Relevance
“…Other components include menthofuran, 1,8-cineol, terpenoids, and flavonoids such as eriocitrin, hesperidin, and kaempferol 7-O-rutinoside [35]. The main cellular receptor for peppermint odor is transient receptor potential cation channel subfamily A member 1, which is associated with AD [36,37]. Peppermint (Mentha piperita) essential oil, which has high levels of menthol/menthone and characteristic in vitro cholinergic inhibitory, calcium regulatory, and GABAA/nicotinic receptor-binding properties, beneficially modulated performance on demanding cognitive tasks and attenuated the increase in mental fatigue associated with extended cognitive task performance in healthy adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other components include menthofuran, 1,8-cineol, terpenoids, and flavonoids such as eriocitrin, hesperidin, and kaempferol 7-O-rutinoside [35]. The main cellular receptor for peppermint odor is transient receptor potential cation channel subfamily A member 1, which is associated with AD [36,37]. Peppermint (Mentha piperita) essential oil, which has high levels of menthol/menthone and characteristic in vitro cholinergic inhibitory, calcium regulatory, and GABAA/nicotinic receptor-binding properties, beneficially modulated performance on demanding cognitive tasks and attenuated the increase in mental fatigue associated with extended cognitive task performance in healthy adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…Since TRPA1 can be triggered by several noxious stimuli, including inflammation, tissue damage or oxidative stress on one hand, and astrocytes influence the extent of this toxin-induced demyelination on the other [29], we assumed that this receptor might modulate the demyelination process. Numerous earlier studies have provided substantial morphological and functional evidence that astrocytes express the TRPA1 receptor, functioning as a regulator of resting Ca 2+ levels [8,9,24,30,31]. In a very recent study, Oh et al, using the cell-type-specific gene-silencing and ultrasensitive sniffer-patch techniques, identified astrocytes as the cellular target and TRPA1 as the molecular sensor for the low intensity, low frequency ultrasound (LILFU).…”
Section: Discussionmentioning
confidence: 99%
“…They detected the functional expression of TRPA1 on oligodendrocytes and showed that ischemia-induced demyelination was diminished in the lack of TRPA1 receptors [11]. Likewise, another group showed that in TRPA1 receptor gene-deleted mice behavioral deficits and neuroinflammation were less severe in a transgenic mouse model of Alzheimer's disease [24]. The same group also later demonstrated that the loss of TRPA1 is associated with decreased anxiety-like behavior and improved performance in spatial memory and social discrimination tests [25].Based on these prior data we focused on further elucidating the role of TRPA1 receptors in the cuprizone model.…”
mentioning
confidence: 99%
“…Similar to its involvement in other tissues and organs, cortical TRPA1 may contribute to physiological functions such as signal processing in sensory cortex and motor behaviours or in developing pathologies such as in Alzheimer's disease [65], brain oedema or oxidative-stress induced neuronal damage.…”
Section: Discussionmentioning
confidence: 99%